Mycorrhizae: Implications for Environmental Remediation and Resource Conservation - Jyotsna Sharma; Andrew V. Ogram; Abid Al-Agely (EDIS)
ENH-1086, a 5-page fact sheet by J. Sharma, A.V. Ogram, and A. Al-Agely, describes the symbiotic relationships between plant roots and fungi and how the resulting rhizosphere activity can lead to transformation and removal of polluting compounds from the soil, reduce the need for fertilizer in commercial nurseries, and improve soil structure and health. Includes references. Published by the UF Department of Environmental Horticulture, November 2007.